The Effect of Multimodal Learning (Text, Audio, and Video) on Students’ Indonesian Language Learning Outcomes: Pengaruh Multimodal Learning (teks, audio, video) terhadap Hasil Belajar Bahasa Indonesia - Suci Marselina; Mac Aditiwarman; Iqlima Zahari; Al Padli; Silvia Rahayu (The Future of Education Journal, 2026)
This study aims to analyze the effect of implementing multimodal learning that integrates text, audio, and video on elementary school students’ Indonesian language learning outcomes. Literacy challenges in the digital era require innovative learning media capable of accommodating students’ diverse cognitive styles. This study employed a quasi-experimental method using a non-equivalent control group design. The research population consisted of upper-grade elementary school students from one school cluster in Sungai Penuh City, Jambi, with a sample of 60 students selected through purposive sampling. Data were collected using learning outcome test instruments and analyzed through an independent samples t-test and N-Gain calculation. The results indicate that the experimental group achieved an average post-test score of 87.50 with an N-Gain value of 0.70 (high category), significantly outperforming the control group, which obtained an average score of 71.10 with an N-Gain value of 0.39 (moderate category). The hypothesis testing results showed a significance value of 0.000 (p < 0.05), confirming a significant effect of the use of multimodal media. The findings of this study emphasize that the integration of various modes of representation is effective in improving students’ comprehension and information retention. Therefore, multimodal learning is recommended as a primary instructional strategy in language learning at the elementary school level.